Optimization of Nutrition Improvement of Preschool Children in the Pandemic Era in Taman Bermain Tabitha, Deli Serdang - Sitorus, Mega Sari; Lubis, Nenni Dwi Aprianti; Anggraini, Dwi Rita; Panggabean, Yoan Carolina (Talenta Publisher, 2023)
The state of good nutrition affects children's health which has a long lasting impact on forming a healthy generation of Indonesians. Nutritional problems, one of which is stunting, is a problem that is of concern to the state, this situation can be caused by lack of knowledge of the mother or inadequate intake. One of the efforts that can be made to overcome is prepared community service at the Tabitha Deli Serdang Playground in the form of nutritional counseling activities, giving healthy food, demonstrations of healthy food processing and making proper hand washing facilities. The problems reported at partner locations was stunting case were found and health service facilities was distant. Data collection on mother's knowledge about nutrition and healthy food was also carried out through filling out questionnaires before and after service. It was found that all mother's knowledge increased significantly after counseling.